Progressive Cone Dysfunction and Geographic Atrophy of the Macula in Late Stage Autosomal Dominant Vitreoretinochoroidopathy (ADVIRC). (2nd January 2016) - Chen, Connie June; Goldberg, Morton F.
Abstract: Autosomal dominant vitreoretinochoroidopathy (ADVIRC) is a rare inherited ocular disease associated with distinct mutations in the BEST1 gene. Typically, patients have only mild visual impairment, and rarely do patients have moderate or severe visual impairment, often as a result of vitreous hemorrhage. We now describe progressive central macular atrophy and cone dysfunction leading to visual loss in an elderly ADVIRC patient 33 years after initial presentation.